A voz do outro: classificação, governamento e fabricação da infância anormal escolar nos discursos médico-pedagógicos (1900-1920) - Nascimento, Pávula Maria Sales (2020)
In Brazil, discussions about normality and abnormality in childhood have spanned the fields of medicine and education since the 19th century, through the constitution of psychiatric knowledge and, simultaneously, through the processes of formalization of the educational field in the country. These debates can be perceived both in the attempts to educate children who were institutionalized in hospitals or hospices and in the efforts to create differentiation strategies between those considered normal and abnormal in regular schools. This research deals with the hybrid field between medicine and education, where childhood, as the object of analysis, differentiation, and classification for the constitution of a disciplinary, control and security society, is the product of the governance actions developed since the Modern Era, holding a manufacturing character. The argument presented herein is that, in the first two decades of the 20th century, a truth regime emerges around abnormal childhood and abnormal school behavior that would support the manufacture of a "school abnormal" in Brazil. Thus, the main objective of this work is to problematize the concept of abnormal childhood and of the governance techniques related to education designed for this childhood. To this end, we chose as the source of analysis two discursive matrices that shaped what was manufactured as the "school abnormal" in Brazil, namely Ulysses Pernambucano’s dissertation (1918) and two publications by Baltazar Vieira de Mello (1917). The time frame was chosen based on the publication parameters of the selected works, as well as on the understanding that these were, among others, pioneers in discussing the issue. On the other hand, the choice of authors is based on a common topic found in these works: the need to differentiate "school abnormality" from other types of "abnormality". Through the historical analysis of the conditions of discourse production that instituted this childhood, it was possible not only to explore how these discourses emerged, but also to problematize the ways in which they became truth regimes about the limits between what is "normal" and "abnormal". Under the aegis of Foucaultian archaeogenealogy, we sought to explain how the discursive practices of doctors and educators were engendered to turn "abnormal childhood education" into a field of knowledge in the 20th century. Therefore, this thesis questions the concept of abnormal school childhood and the political and educational technologies fabricated for the governance of children seen as abnormal, "indomitable", "turbulent", "trouble", "difficult", "maladjusted", "late", "idiots", "imbeciles", "retarded", reflecting on the paths that were conceived for this childhood and what conductions positioned it within our society.